Supply chain analysis of silage in Chitwan district of Nepal - Subedi, Sanjiv; Timsina, Krishna Prasad; Sapkota, Sudha; Chhetri, Jyoti (Journal of Agriculture and Natural Resources, 2024)
Silage, anaerobically fermented green fodder, is valued worldwide as a source of animal feed during lean months. No studies have yet been documented exploring the supply chain map of silage and production economics of fodder used. Also, identification and prioritization of the major problems associated with fodder maize production, silage production and marketing is necessary. Chitwan district was purposively selected for this study as there are a greater number of commercial dairy cattle farms and silage-making agro-industries. A field survey and FGD was conducted among the fodder maize gowing farmers, Key Informant Interview was taken with the owner of six different silage producing farms during the time period between September, 2023 to February, 2024. A total of 90 sample farmers were selected for the study by applying the simple random sampling technique. The average productivity of the fodder maize was 539 qt/ha. The average land holding of the farmers growing fodder maize was found to be 0.38 ha. Moreover, the average price of the fodder maize was estimated NRs.345/qt. The positive gross margin and benefit cost ratio (BCR) greater than one showed both fooder maize production and silage production profitable and financially viable enterprises. Indexing identified the inadequate availability of fertilizers in time and the low price of fodder maize in the market as the first major problems associated with fodder maize production and marketing respectively. The role of cooperatives seemed to be important in the backward and forward linkages of silage as cooperatives were found to be closely associated with the marketing of fodder maize and silage as well. Assuring the timely availability of fertilizers, quality seed of suitable varieties and irrigation facilities must be the priority areras of government intervention to enahcne the production of fodder maize and silage. Moreover, price favour for the farmers, prioritizing the development of marketing channels, assuring the availability of market information, developing the transportation and storage facilities seemed to be primary areas of intervention to promote and strengthen the supply chain of silage. Assessing the demand for silage and exploring the more sustainable value chain could be an important area for further research.